Siegfried Kracauer y la emergente cultura de masas (2014)
ABSTRACT: 20th century begins with a great turbulence. In The Weimar Republic, Siegfried Kracauer glimpses it like no other, from a change in taste, of a new subject that emerges and appropiates himself of the reigning confusión: the mass. Massive spectacle and cinema make an aesthetization of the serial, prevailing logics, and instrumental rationality extends itself to the sphere of the quotidian in that cultural consumption. This paper pretends to present the developments and procedures of Kracauer in order to show the social state of his present, novelty and contradiction.